Clergy education in America: religious leadership and American public life - Golemon, Larry A. (Oxford scholarship online, 2021)
In 'Clergy Education in America', Larry Golemon shows not only how our conception of professionalism in religious life has changed over time, but also how the education of religious leaders has influenced American culture. Tracing the history of clergy education in America from the Early Republic through the first decades of the twentieth century, this text offers a sweeping look at an oft-overlooked but critically important aspect of American public life.